2012
DOI: 10.2495/hpsm120111
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic properties of auxetic foams

Abstract: Auxetic foams have raised some interest in noise and vibration control applications as they showed unusual acoustic properties compared to conventional ones, particularly at low frequencies. Auxetic foams are porous materials with a negative Poisson's ratio. They expand in all directions when only pulled in one. In this paper, the acoustic properties of auxetic foams are described both from a numerical and experimental point of view. The acoustic absorption properties of both auxetic and conventional foam samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…From the viewpoint of mechanical property, auxetic materials possess higher shear modulus, greater indentation resistance, better energy absorption ability, and stronger crack resistance than the conventional materials 13,14 . From the viewpoint of acoustic property, auxetic porous metamaterials exhibit better low‐frequency sound absorption property than conventional porous materials 15,16,17 . Also, the auxetic phononic crystals are demonstrated to have lower frequency phononic bandgaps than phononic crystals with positive Poisson's ratio 18 …”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of mechanical property, auxetic materials possess higher shear modulus, greater indentation resistance, better energy absorption ability, and stronger crack resistance than the conventional materials 13,14 . From the viewpoint of acoustic property, auxetic porous metamaterials exhibit better low‐frequency sound absorption property than conventional porous materials 15,16,17 . Also, the auxetic phononic crystals are demonstrated to have lower frequency phononic bandgaps than phononic crystals with positive Poisson's ratio 18 …”
Section: Introductionmentioning
confidence: 99%
“…Other enhanced properties are mechanical hardness, toughness, and stiffness [ 11 ]. In terms of the dynamic performance, auxetic materials also show an overall superiority regarding damping and acoustic properties compared to the conventional materials [ 12 , 13 ]. It has been found that auxetic honeycomb structures not only show an improvement of transmission loss factors but also show an isotropic acoustic signature at lower modes and also have isotropic mechanical properties [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of the acoustic properties of polyolefin foams are limited to the study of sound absorption under various conditions and its dependence on porosity, apparent density, tortuosity of pores, and radiation frequency [1][2][3][4][5][6][7][8][9]. A number of studies [1][2][3][4][5][6][7][8][9] show the possibility of improving the acoustic characteristics (sound absorption, sound attenuation, and vibration damping property) by optimizing the structure and synthetic formula with various inorganic and organic fillers [3,[10][11][12][13]. The influence of porosity and tortuosity of pores on the speed of sound, Poisson's ratio, elastic modulus, and radiation frequencies is studied [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%